The Effectiveness of a Training Program Based on Self-Management Skills in Developing Independent Behavior and Safety and Security Skills of Children with Intellectual Disability - Eltantawy, Mahmoud Mohamed (Journal of Intellectual Disability - Diagnosis and Treatment, 2023)
Background: Children with intellectual disabilities suffer from many deficiencies that negatively affect their adaptation and transition from one stage to another. Objective: The current study aimed at developing independent behavior, safety, and security skills of children with an intellectual disability through a program based on self-management skills. Methods: The study sample consisted of (20) children with mild intellectual disabilities enrolled in classes from the fourth to the sixth primary. The sample was divided into two groups; the experimental group to which the training program has been applied, consisting of (10) children, and the control group (10) children. The study relied on the quasi-experimental method. As such, the training program is perceived to be the independent variable, while the independent behavior, safety, and security skills are considered the dependent ones. The study is based on a number of tools that are prepared by the researcher, the scale of independent behavior of children with intellectual disabilities, the scale of safety and security skills of children with intellectual disabilities, and the training program based on self-management skills. Results: The study’s results disclosed the effectiveness of the training program used in developing independent behavior and safety and security skills of children with intellectual disabilities. Conclusions: The effectiveness of self-management strategies such as self-monitoring, self-reinforcement, self-instruction, and problem-solving in developing the independent behavior and security and safety skills of children with intellectual disabilities has been proven.